Composite of graphene oxide and porous polymer metal complex, molded body of the composite, method for producing the composite, gas adsorbent, gas separation device, and gas storage device

By combining graphite oxide with porous polymer metal complexes and dispersing them in aqueous solution to partial contact or cross-connection, the problem of specific collapse or crushing of the mold is solved, and the stability and efficiency of the gas adsorption and separation system are achieved.

JP7660829B2Active Publication Date: 2025-04-14NIPPON STEEL CORPORATION +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020140735
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-24
Publication Date
2025-04-14
Estimated Expiration
2040-08-24

AI Technical Summary

Technical Problem

The prior art is difficult to prevent the molds of porous polymer metal complexes from collapsing or crushing while maintaining the gas adsorption capacity, especially in gas adsorption and separation systems.

Method used

By combining the appropriate amount of graphite oxide with porous polymer metal complexes, a method is used to disperse the graphite oxide in aqueous solution, thereby partially contacting or cross-connecting with the porous polymer metal complexes to form a more stable mold specificity.

Benefits of technology

The mold-specific stability and gas adsorption performance are achieved, which avoids collapse or crushing, while maintaining efficient gas separation and storage capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660829000008
    Figure 0007660829000008
  • Figure 0007660829000009
    Figure 0007660829000009
  • Figure 0007660829000010
    Figure 0007660829000010
Patent Text Reader

Abstract

To provide a molded article of a porous polymer metal complex hardly causing collapse and pulverization of the molded article when the molded article is formed.SOLUTION: A composite comprises a graphene oxide and a porous polymer metal complex.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite of graphene oxides and a porous polymer metal complex (also known as a porous coordination polymer (PCP)), a method for producing the composite, a molded body of the composite, a gas adsorbent made of the molded body, and a gas separation device and a gas storage device using the gas adsorbent. [Background technology]

[0002] Porous polymer metal complexes are crystalline solids obtained from metal ions and organic ligands, and due to the variety of combinations of metal ions and organic ligands and the diversity of framework structures, they have the potential for use as catalysts, gas storage, and separation materials (see Patent Document 1 and Non-Patent Document 1).

[0003] The porous polymer metal complex is usually obtained as a powder or fine particles, and can be used as a gas adsorbent due to its structural characteristics. In industrial applications, powders are generally difficult to handle. When using this powder as a catalyst, for example, it is possible to easily separate the product and catalyst after the reaction by preparing it as a heterogeneous catalyst supported on a solid material.

[0004] A typical method for gas separation using a solid adsorbent is the pressure swing adsorption method (hereinafter, simply referred to as "PSA system"). Since this system is a gas flow type system, it is preferable that the adsorbent used in this system is a porous polymer metal complex formed into a certain shape so that it does not scatter with the gas flow. As a gas storage material or separation material used in the PSA system, for example, existing zeolite can be mentioned, but since this is usually a fine powder immediately after production, it is often formed into granules or columns of 1 mm or more. When forming zeolite, both methods using a binder and methods not using a binder are known. When using a binder, sugars and the like are generally used.

[0005] When compacts such as powders are used industrially, the collapse and pulverization of the compacts can cause various inconveniences. When using a catalyst, this can cause the catalyst to become mixed into the reaction product. In the case of a PSA system, this can cause pipe blockages and solenoid valve malfunctions. In other words, it is important that the compacts maintain their shape during use. When using the compacts for gas adsorption purposes, it is also important that the gas adsorption capacity is not reduced due to the gas diffusion into the compact being hindered.

[0006] In order to prevent the compact from collapsing or pulverizing, it is preferable to compress the powder highly to form it or to use a strong binder, but the compact obtained in this way has a slow gas diffusion and is not suitable as an adsorption or separation material. In particular, compared to porous bodies such as zeolite and activated carbon, porous polymer metal complexes are compounds in which metal ions and organic ligands are bonded by weak coordinate bonds, so they have low mechanical strength and are known to deteriorate under high compression or shear force. For this reason, the formation of gas adsorbents is required to achieve both the contradictory properties of preventing the compact from collapsing or pulverizing and slowing down gas diffusion. For this purpose, a forming method using a binder, etc. is also known, rather than simply forming the compact by compressing the powder. However, even in this case, it is required to use an appropriate amount of a binder that does not cause the compact to collapse or pulverize during use, does not hinder gas diffusion, and does not interact with the gas adsorbent to reduce the gas adsorption ability of the gas adsorbent. Like zeolite, porous polymer metal complexes are in the form of fine powder immediately after production, and so in order to use them as adsorbents in PSA systems, they must be molded, just like zeolite, and methods of molding them into granules, tablets, etc., with or without a binder are known (see Patent Document 2).

[0007] As a method for producing a molded article of a porous polymer metal complex, formation of a complex with a polystyrene oligomer has been proposed (see Non-Patent Document 2). However, there is no information regarding the shape retention and powdering of the complex.

[0008] In addition, some porous polymer metal complexes are called "flexible porous polymer metal complexes" whose structure changes with gas adsorption and desorption. Many of these flexible porous polymer metal complexes show gate-type adsorption and desorption, in which the amount of gas adsorbed responds nonlinearly to pressure.

[0009] Since these flexible porous polymer metal complexes undergo structural changes in response to gas adsorption and desorption, compacts that do not use binders or compacts that use binders that cannot keep up with the structural changes will collapse and pulverize after gas adsorption. If the compact collapses or pulverizes, the piping, solenoid valves, etc. of the PSA system will become clogged or malfunction, so it has been proposed to use a flexible resin as a binder to shape the flexible porous polymer metal complexes (see Patent Document 3 and Non-Patent Document 3). Moreover, Patent Document 4 proposes using pulp fibers as a binder to give a shape to a flexible porous polymer metal complex.

[0010] However, these resins are not porous materials and have low gas permeability, so there is a problem that the gas adsorption rate decreases. In addition, even if the resin has flexibility, it is hard at room temperature and cannot follow the structural change of the porous polymer metal complex, and as a result, the structural change of the flexible porous polymer metal complex is suppressed, and problems such as a decrease in the gas adsorption amount tend to occur. In fact, in the description of Non-Patent Document 3, the gas adsorption amount before molding is 300 mL / g, and the polyvinyl alcohol content of the molded body is 15%, so the gas adsorption amount of the molded body should be 255 mL / g, but the observed value is only 200 mL / g, and the gas adsorption property was reduced by nearly 20% by forming the molded body. In addition, the porous polymer metal complex in this document is described as having flexibility, but the isotherm shown in Figure 4 in the document was type I. Since this does not show the gate-type isotherm shown by a typical flexible porous polymer metal complex, it is unclear whether it can be applied as a gate-type flexible porous polymer metal complex. In addition, the shape retention after gas adsorption and desorption is also unclear.

[0011] A gate-type porous polymer metal complex is a material that exhibits a gate-type isotherm (gate phenomenon). A gate-type isotherm refers to an adsorption or desorption isotherm that shows an inflection point as shown in Figure 1, mainly due to a change in the structure of the porous polymer metal complex. As shown in Figure 1, the isotherm of a gate-type porous polymer metal complex is specified by the adsorption start gate pressure, adsorption completion gate pressure, gate adsorption amount, desorption start gate pressure, desorption completion gate pressure, and gate desorption amount.

[0012] As another method for forming a porous polymer metal complex, Non-Patent Document 4 discloses a composite of a porous polymer metal complex and graphenes produced by a so-called in situ method, in which a porous polymer metal complex is synthesized in the presence of graphenes. However, in this method, graphenes are added to a solution in which the metal salt and ligand, which are the raw materials of the porous polymer metal complex, are mixed to synthesize the porous polymer metal complex, and the reactivity of the metal salt and the ligand may change, which may reduce the yield of the porous polymer metal complex. In addition, the adsorption properties of the obtained porous polymer metal complex may be reduced. Furthermore, under the synthesis conditions, particularly when the solvent is highly hydrophobic, the graphenes may associate, stack, and form into multiple layers, which may reduce the inherent properties of graphene, and may reduce moldability and adsorption.

[0013] A typical method for synthesizing a composite is to mix solid graphenes with solid porous polymer metal complexes. However, since graphenes are in a multi-layered state in the solid state, it is not easy to form a composite with a porous polymer metal complex, and as a result, the moldability and adsorption properties may be reduced.

[0014] Patent Document 5 describes a method for producing a zeolite separation membrane having gas adsorption properties by reacting zeolites with graphenes in an aqueous solution. It also describes that in order to synthesize the desired zeolite separation membrane, the surface charge density of the zeolite is changed by changing the pH with an additive or the like.

[0015] Many porous polymer metal complexes have a structure completely different from that of zeolites. Zeolites are ionic inorganic materials consisting of silicon, aluminum, etc. and oxygen, whereas porous polymer metal complexes are porous bodies formed by coordinate bonds between metal ions and organic ligands. For this reason, they have a surface charge completely different from that of zeolites, and since the ligands of many porous polymer metal complexes contain aromatic rings, there is a strong interaction between the aromatic rings and graphenes. Patent Document 5 does not describe porous polymer metal complexes. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] JP 2000-109493 A [Patent Document 2] JP 2015-66512 A [Patent Document 3] International Publication No. 2015 / 012373 [Patent Document 4] JP 2018-153740 A [Patent Document 5] JP 2018-192378 A [Non-patent literature]

[0017] [Non-Patent Document 1] Kitagawa, Susumu (2001). Accumulated metal complexes. Kodansha Scientific, pp. 214-218. [Non-Patent Document 2] Livingston et al., J.Am.Chem.Soc.(2013) 15201 [Non-Patent Document 3] Vos et al., Microporous and mesoporous mater, (2009)221 [Non-Patent Document 4] In situ synthesis, Bandosz et al., J. Col. Int. Sci. (2015) 139.J Summary of the Invention [Problem to be solved by the invention]

[0018] An object of the present invention is to provide a composite of a porous polymer metal complex and graphene oxides, which is resistant to collapse and powdering when formed, and a method for producing the composite, as well as a molded body made of the composite. Another object of the present invention is to provide a composite of a porous polymer metal complex and graphene oxides, which has excellent properties as a gas adsorbent, and a molded body made of the composite. Another object of the present invention is to provide a gas storage device and a gas separation device that house the composite therein. [Means for solving the problem]

[0019] The present inventors have conducted extensive research to solve the problems described above, and have found that a molded body that is less likely to collapse or powder can be produced by combining an appropriate amount of graphene oxides with a porous polymer metal complex using an appropriate method, thereby completing the present invention. In addition, the present invention has been completed by clarifying the correlation between the properties of graphene oxides that do not deteriorate gas adsorption properties and do not cause collapse or powdering of the molded body during use and the properties of the porous polymer metal complex. In addition, the present invention was achieved by clarifying the correlation between the properties of graphene oxides, which do not deteriorate the gas adsorption properties of the porous polymer metal complex and do not cause the compact to collapse or powder during use, and the properties of the porous polymer metal complex.

[0020] Thus, in accordance with the present invention there is provided: (1) A method for producing a flexible porous polymer metal complex comprising the steps of: the flexible porous polymer metal complex is a porous polymer metal complex having a one-dimensional chain structure or a laminated type porous polymer metal complex having a two-dimensional network; The graphene oxides are contained in an amount of 0.01 to 30% by mass, And the composite has infinite electrical resistance. (2) The complex according to (1) above, wherein the flexible porous polymer metal complex having a one-dimensional chain structure is represented by the formula: [G(H)2(I)] (wherein G is a transition metal ion, H is a first ligand, and I is a second ligand), or G2(J)3(L3)4 (wherein G is a transition metal ion, J is a ligand, and L is a monovalent counter ion). (3) The complex according to (1) above, wherein the two-dimensional network layered flexible porous polymer metal complex is a complex having a formula [GH] collectively referred to as a Kagome type (wherein G represents a transition metal ion, and H represents a ligand), or a complex having a formula [GHX2] collectively referred to as an ELM (wherein G represents a transition metal ion, H represents a 4,4-bipyridyl, and X represents a monovalent counter ion). (4) A composite material comprising graphene oxides and a flexible porous polymer metal complex; the flexible porous polymer metal complex is a porous polymer metal complex having a one-dimensional chain structure or a laminated type porous polymer metal complex having a two-dimensional network; A method for producing a composite, the composite containing 0.01 to 30% by mass of graphene oxides, Concentration of 0.001 to 0.100% by mass The aqueous solution containing the graphene oxides is Dispersed in water A method for producing a composite, comprising the step of mixing the flexible porous polymer metal complex. (5) The method for producing a complex according to (4) above, wherein the flexible porous polymer metal complex having a one-dimensional chain structure is represented by the formula: [G(H)2(I)] (wherein G is a transition metal ion, H is a first ligand, and I is a second ligand), or G2(J)3(L3)4 (wherein G is a transition metal ion, J is a ligand, and L is a monovalent counter ion). (6) The method for producing the complex according to (4) above, wherein the two-dimensional network layered flexible porous polymer metal complex is a complex of the formula [GH] (wherein G represents a transition metal ion and H represents a ligand) collectively referred to as Kagome type, or a complex of the formula [GHX2] (wherein G represents a transition metal ion, H represents a 4,4-bipyridyl, and X represents a monovalent counter ion) collectively referred to as ELM. (7) A molded article comprising the composite material according to any one of (1) to (3) above. (8) A gas adsorbent comprising the molded article according to (7) above. (9) A gas separation device using the gas adsorbent described in (8) above. (10) A gas storage device using the gas adsorbent described in (8) above. Effect of the Invention

[0021] The composite of the porous polymer metal complex and graphene oxides of the present invention (hereinafter, simply referred to as the "composite of the present invention") can adsorb and release a large amount of gas, and selectively separate the gas. The composite of the present invention has a powdery or sponge-like property that is difficult to scatter, although the form of the composite varies depending on the amount of graphene oxides blended, and can be easily deformed and processed. The composite of the present invention can be used as a gas adsorbent or separation material as a powder or pelletized form. The composite of the present invention can be supported on another material, such as a hollow fiber or tube, in a solid state or in a dispersion state, to produce a composite in which the composite of the present invention is supported on another material, and this can be used as a gas separation material and device.

[0022] Ma In addition, a gas storage device and a gas separation device can be manufactured by using a gas adsorption material made of a molded body of the porous polymer metal complex composite of the present invention. In addition, since the composite of the present invention forms a stable molded body, it can be used for catalytic reactions.

[0023] The molded article of the porous polymer metal complex composite of the present invention can separate gas very efficiently when used as a gas separation device in, for example, a PSA or TSA (temperature swing adsorption) system. It can also shorten the time required for pressure change, which contributes to energy saving. Furthermore, it can also contribute to the miniaturization of gas separation devices, which not only increases the cost competitiveness when selling high-purity gas as a product, but also reduces the cost required for equipment that requires high-purity gas even when high-purity gas is used within one's own factory, ultimately resulting in an effect of reducing the manufacturing cost of the final product.

[0024] Another application of the molded article of the porous polymer metal complex composite of the present invention is a gas storage device. When the molded article of the porous polymer metal complex composite of the present invention is applied to a gas storage device (such as a gas tank for commercial use, a gas tank for consumer use, or a fuel tank for vehicles), it is possible to dramatically reduce the pressure during transportation or storage. The effect of being able to reduce the gas pressure during transportation or storage is, first of all, the improvement of the degree of freedom in the shape of the gas storage device. In conventional gas storage devices, the gas adsorption amount cannot be maintained high unless the pressure during storage is maintained. However, in the gas storage device of the present invention, a sufficient gas adsorption amount can be maintained even if the pressure is reduced.

[0025] Another application of the molded article of the porous polymer metal complex composite of the present invention is a gas separation device. When the molded article of the porous polymer metal complex composite of the present invention is applied to a gas separation device, the high gas permeability makes it possible to perform gas separation at a lower pressure and high-efficiency gas separation with a large amount of gas produced per hour compared to other materials.

[0026] When the gas adsorbent made of the molded article of the porous polymer metal complex composite of the present invention is applied to a gas separation device or a gas storage device, it is not necessary to use a special device for the container shape, container material, type of gas valve, etc., and it is possible to use those that have been used in gas separation devices and gas storage devices in the past. However, this does not exclude improvements to various devices, and any device used is included in the scope of the present invention as long as it uses the molded article of the porous polymer metal complex of the present invention. [Brief description of the drawings]

[0027] [Figure 1] FIG. 13 is a diagram showing the gate pressures of an adsorbent made of a porous polymer metal complex molded body. [Diagram 2] 1 is an electron microscope photograph of the dispersion state of the graphene oxides and porous polymer metal complex of the present invention in a composite before molding. [Diagram 3]1 is an electron microscope photograph of the dispersion state of the graphene oxides and porous polymer metal complex of the present invention in a composite before molding. [Figure 4] Adsorption isotherms obtained from the complexes prepared using ELM-31b. [Diagram 5] 1 is an electron microscope photograph of the pre-molding dispersion state within the composite of the porous polymer metal complex obtained in Comparative Example 1. [Figure 6] 1 is an electron microscope photograph of the pre-molding dispersion state within the composite of the porous polymer metal complex obtained in Comparative Example 2. [Figure 7] 1 is an electron microscope photograph of the pre-molding dispersion state within the composite of the porous polymer metal complex obtained in Comparative Example 3. [Figure 8] 1 is an electron microscope photograph of the pre-molding dispersed state within the composite of the porous polymer metal complex obtained in Comparative Example 4. [Figure 9] 1 is an electron microscope photograph of the pre-molding dispersion state within the composite of the porous polymer metal complex obtained in Comparative Example 5. [Figure 10] 1 is an electron microscope photograph of the pre-molding dispersion state within the composite of the porous polymer metal complex obtained in Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The porous polymer metal complex used in the composite of the present invention is a porous polymer metal complex consisting of a metal ion such as an alkaline earth metal or a transition metal and a multidentate ligand. The porous polymer metal complex used in the composite of the present invention can absorb and release a large amount of gas by itself, and can selectively adsorb gas.

[0029] Examples of the porous polymer metal complex that can be used in the composite of the present invention include porous polymer metal complexes such as UiO-66-H, ZIF-8, CPO-27(Ni), CAU-10, and UTSA-16.

[0030] UiO-66-H is a porous polymeric metal complex with three-dimensional pores, represented by the following formula [Zr6O4(OH)4(BDC)6] and described in the non-patent literature (Lillerud et al., Chem. Mater. (2014) 4068).

[0031] ZIF-8 is represented by the formula: [Zn(mim)2] (mim is an ionized form of 2-methylimidazole) and is a porous polymeric metal complex having three-dimensional pores, described in non-patent literature (Wiebcke et al., Chem. Mater. (2011) 2142).

[0032] CPO-27(Ni) is represented by the formula: [Ni(C8H4O6)2] (C8H4O6 is ionized 2,5-dihydroxyterephthalic acid), and is a porous polymeric metal complex having one-dimensional pores, which is described in a non-patent document (Matzger et al., J. Am. Chem. Soc. (2008) 10870).

[0033] CAU-10 is a porous polymeric metal complex with one-dimensional pores, represented by the formula: [Fe2(C8H4O4)2] (C8H4O4 is ionized isophthalic acid), and described in the non-patent literature (Stock et al., Chem. Mater. (2013) 17).

[0034] UTSA-16 is a porous polymeric metal complex with three-dimensional pores, represented by the formula: [K2Co3(cit)2] (cit is ionized citric acid) and described in non-patent literature (Han et al., Chem. Eng. Sci. (2019) 813).

[0035] Further, examples of the porous polymer metal complex used in the present invention include flexible porous polymer metal complexes consisting of metal ions such as alkaline earth metals and transition metals and multidentate ligands, and have a one-dimensional, two-dimensional or three-dimensional network structure.

[0036] The flexible porous polymer metal complex means a porous polymer metal complex whose structure changes over time when gas is adsorbed and desorbed. The change in structure can be confirmed by powder X-ray diffraction measurement or the like.

[0037] The adsorbent including a molded body made of a flexible porous polymer metal complex composite that can be used in the composite of the present invention shows an adsorption isotherm shown in Figure 1. Existing materials such as activated carbon and zeolite and most porous polymer metal complexes show adsorption isotherms that are convex upward or close to a straight line, whereas gate-type gas adsorption is a phenomenon in which the amount of gas adsorbed increases rapidly when a certain gas pressure is exceeded, and in the case of desorption, the amount of gas adsorbed decreases rapidly below a certain gas pressure. This is thought to be due to the flexibility of the structure of the porous polymer metal complex, which changes the structure to one that is more likely to absorb gas by adsorption of gas (in the case of adsorption), or changes the structure to one that is less likely to absorb gas by releasing a certain amount of gas (in the case of desorption), resulting in a sudden change in the amount of gas adsorbed.

[0038] Examples of the porous polymer metal complex having flexibility include a porous polymer metal complex having a one-dimensional chain structure, for example, a porous polymer metal complex having a one-dimensional chain interlocking structure. Specifically, the compound 1a represented by the formula: [Cu(dhbc)2(4,4'-bpy)]H2O described in Angew, Chem. Int. Ed. (2003) 428 by Kitagawa et al., and the compound Ni2(4,4'-bipyridine)3(NO3)4 described in J. Am. Chem. Soc. (2001) 10001 by Rosseinsky et al. are exemplified. In the present invention, a porous polymer metal complex having an interlocking structure is exemplified, but an interlocking structure is not necessarily required. It is known that when there are no bonds such as a large number of hydrogen bonds between the one-dimensional chains, the interaction between the chains is weakened and the porous polymer metal complex exhibits flexibility.

[0039] An example of a flexible porous polymer metal complex is a two-dimensional network laminated type porous polymer metal complex. A two-dimensional laminated porous polymer metal complex is a porous polymer metal complex in which the network structure of the porous polymer metal complex has a two-dimensional layered structure, and this structure is formed by laminating weak interactions such as van der Waals forces and hydrogen bonds. Compared to three-dimensional flexible porous polymer metal complexes, volume expansion occurs only in a specific direction (the direction in which the layers expand), so the molded product is more susceptible to stress.

[0040] Specifically, examples of the ELMs include elastic layer-structured metal organic frameworks (ELMs) represented by the following formula (X), which are stacks of square lattices with 4,4'-bipyridine (bpy) as a ligand. Examples of ELMs include ELM-11, ELM-12, ELM-12 / 3, ELM-13, ELM-22, ELM-31, etc., as exemplified by Ueshiro et al., Int. J. Mol. Sci. 2010, 3803.

[0041] [MA2B](X) (In the formula, M is a transition metal ion, A is a counter ion, B is a bpy ligand, and X represents a molecule such as a solvent present in the pores.)

[0042] Another example of a porous polymer metal complex having flexibility and having a layered structure of a two-dimensional network is a Kagome-type porous polymer metal complex.

[0043] The kagome-type porous polymer metal complex is represented by the following formula. [DE] (In the formula, D is a divalent transition metal ion, and E is a substituted or unsubstituted isophthalic acid ion.)

[0044] Kagome-type porous polymer metal complexes are disclosed, for example, in the following documents. In JP 2012-228667 A, a compound having the general formula: {M(OOC-R-COO}2 (wherein M is Cu 2+ , Zn 2+ , Ru 2+ , Rh 2+ , Mo 2+, Cr 2+ and R represents a divalent aromatic group in which two COOH groups are in a meta-position relationship.

[0045] Sato et al., Science, (2014) 167, describes a porous polymer metal complex collectively known as the Kagome type, which is composed of copper ions and isophthalic acid ions substituted with azide groups.

[0046] Zaworotko et al., Chem. Commun. (2004) 2534, describes a porous polymer metal complex composed of copper ions and isophthalic acid ions having benzyloxy groups as substituents.

[0047] Zaworotko et al., Angew. Chem. Int. Ed. (2001), 2111, describes porous polymer metal complexes collectively known as kagome structures, which are composed of zinc or copper ions and isophthalic acid. Note that the pyridine represented by py is only weakly coordinated to the metal ion and is removed during pretreatment for adsorption measurements, so the network structure can be considered a general kagome structure.

[0048] Zaworotko et al., Cryst. Growth Des. (2003) 513, describes porous polymer metal complexes collectively known as kagome structures, which are composed of copper ions and isophthalic acid ions or isophthalic acid ions substituted with ethoxy groups.

[0049] JP 2012-045533 A describes a compound of the general formula: [Cu2(pyridine-3,5-dicarboxylate)2] n The porous polymer metal complexes represented by the following formula are generally called Kagome type.

[0050] In U.S. Patent Application Publication No. 2002 / 120165,

[0022] , there is described a compound having the general formula (MA) synthesized from the ligand shown in FIG. n(wherein M represents any metal and A represents a difunctional carboxylate), and is generally known as a Kagome-type porous polymer metal complex.

[0051] As examples of the two-dimensional network laminated type, the porous polymer metal complexes collectively called Kagome type and ELM are given, but the flexible two-dimensional network laminated type porous polymer metal complexes are not limited to these. It is known that when there are no bonds such as hydrogen bonds between layers, as in the Kagome type and ELM given as examples, the interaction between the layers is weakened and the porous polymer metal complex shows flexibility.

[0052] Furthermore, an example of a flexible porous polymer metal complex is a three-dimensional network laminated type porous polymer metal complex.

[0053] Specific examples of porous polymer metal complexes with flexible three-dimensional networks include a group of porous polymer metal complexes synthesized from divalent or trivalent metal ions such as iron or aluminum and terephthalic acids, commonly known as MILs, as described in Fuchs et al., Angew. Chem. Int. Ed. (2009), 8314, etc.

[0054] Specific examples of other three-dimensional network porous polymer metal complexes are disclosed in the following documents. Examples include porous polymer metal complexes represented by Ni2(2,6-ndc)2dabco, which are synthesized from divalent transition metals such as nickel, naphthalenedicarboxylic acid, 1,8-diazabicyclooctane (DABCO), etc., collectively referred to as DUT, as described in Kaskel et al., Phys.Chem.Chem.Phys.(2015)17471. In addition, Kitagawa et al., Chem.Soc.Rev.(2005)109, describe porous polymer metal complexes represented by compound numbers 9, 10, and 11, which are synthesized from copper ions and divalent carboxylic acid pzdc and dpyg ligands, or from copper ions and pymo, a ligand containing two pyridine-type nitrogens, or from chromium (III) ions and terephthalic acid, BDC ligand. Kitagawa et al., J. Solid State Chem. (2005) 2420, describes a flexible porous polymer metal complex represented by the compound name CPL-2, which is represented by [Cu2(pzdc)2(bpy)].

[0055] As examples of three-dimensional network porous polymer metal complexes, the porous polymer metal complexes collectively called MIL and DUT are given, but the flexible three-dimensional network laminated porous polymer metal complexes are not limited to these. In the case of a network formed of a rigid ligand having a certain length such as terephthalic acid, as in the examples of MIL and DUT, it is known that the porous polymer metal complex exhibits flexibility by changing the angle of the coordination structure around the metal ion.

[0056] The flexible porous polymer metal complex has a characteristic that the lattice structure of the porous polymer metal complex changes when gas is adsorbed and desorbed, but the correlation between the degree of change in the lattice structure and the degree of volume change of the material is not generally known. However, the volume change of the material accompanying gas adsorption and desorption and the degree of the volume change of the material can be measured by filling a tube with the material, adsorbing and desorbing gas, and measuring the volume change, as shown in Figure 3 of Kondo et al. Nano Lett. (2006) 2581.

[0057] The composite of the present invention includes graphene oxides. As used herein, "graphene oxides" means that graphene oxide may contain a small amount of graphene. Graphene oxide may naturally return to graphene in part due to contact with an organic solvent or heat. For this reason, graphene oxide prepared from prepared graphene may contain a small amount of graphene. In this specification, this state is referred to as graphene oxides.

[0058] FIG. 2 is an electron microscope photograph of the dispersion state of the raw material before molding of the composite of graphene oxides and porous polymer metal complex of the present invention. The particles are porous polymer metal complex particles. In the composite of the present invention, as shown in FIG. 2, the porous polymer metal complex does not need to be bound without gaps by the graphene oxides spread in a film shape, but is partially in contact with the graphene oxides. In addition, as shown in FIG. 3, some of the crystal particles of the porous polymer metal complex may be crosslinked by the graphene oxides deformed into a rod shape or a cylinder shape. The porous polymer metal complex contains a benzene ring as a ligand, similar to the benzene ring of the constituent element of the graphene oxides. As a result, it is considered that since the affinity with the graphene oxides is high, sufficient interaction occurs between the graphene oxides and the porous polymer metal complex even in partial contact, resulting in moldability.

[0059] In the composite of the present invention, the porous polymer metal complex does not need to be bound by the graphene oxides without gaps, but is partially in contact with them. Therefore, the diameter of the graphene oxides may be smaller than the diameter of the crystal particles of the porous polymer metal complex. In addition, graphene oxides having various diameters can be used in the present invention, and specifically, graphene oxides having a diameter of 10 micrometers to 1 mm can be exemplified. The size of the graphene oxides can be determined by SEM or the like. As long as graphene oxide of this size can be obtained, various graphites can be used as the raw material for synthesizing graphene oxide.

[0060] In the present invention, the porous polymer metal complex crystal particles may be partially in contact with the graphene oxides. Therefore, the porous polymer metal complex can use crystal particles of various sizes. The size of the porous polymer metal complex crystal particles that can be used in the present invention is determined not by the primary particle size when the crystal particles have an aggregated structure, but by the aggregated structure, i.e., the diameter of the secondary particles. In order for the porous polymer metal complex particles to partially contact the graphene oxides, the diameter of the graphene oxides is preferably 3 to 5000 times the diameter of the secondary particles of the porous polymer metal complex. If it is less than 3 times, the contact with the graphene oxides is poor, and if it is more than 5000 times, the gas adsorption ability of the porous polymer metal complex crystal particles is inhibited by the excess graphene oxide, and the adsorption characteristics are reduced. If the crystal particle size of the porous polymer metal complex is large, it can be used by reducing the particle size by grinding or pulverizing with a homogenizer or the like.

[0061] The composite of the present invention is produced by mixing a porous polymer metal complex with an aqueous solution containing graphene oxide (hereinafter referred to as "GO").

[0062] When producing the composite of the present invention, it is preferable to produce it using an aqueous solvent. The graphene oxides used in the present invention are synthesized by an oxidation reaction and have oxygen-containing functional groups, so they have high affinity with water. By using an aqueous solvent, the association of graphene oxide is reduced, and the synthesis of the composite proceeds quickly. When a non-aqueous organic solvent is used, graphene oxide associates in the non-aqueous organic solvent, the degree of stacking increases, and the graphene oxide becomes thick, so that it does not come into sufficient contact with the crystal particles of the porous polymer metal complex. As the aqueous solvent, water and a mixed solvent of water and an organic solvent are preferable, and in the case of a mixed solvent, a solvent containing 20% ​​or more of water is preferable. In this case, examples of the organic solvent include alcohols such as methanol and ethanol, and solvents that are miscible with water, such as tetrahydrofuran, dimethylformamide, and acetonitrile.

[0063] In order to impart moldability to the crystal particles of the porous polymer metal complex, it is important to add an appropriate amount of GO relative to the amount of the crystal particles so that GO comes into contact with the surface of the crystal particles even partially. For this purpose, the concentration of the GO aqueous solution (GO mass%) is 0.0001 to 20 mass%, preferably 0.001 to 10 mass%. When the concentration of the GO aqueous solution is low, the aggregation of GO molecules in the GO solution is reduced, and as a result, a good composite is obtained, but the amount of the GO aqueous solution required is huge, and workability is reduced. When the GO concentration is too high, the aggregation of GO molecules in the GO solution increases. Therefore, the actual GO concentration decreases, the contact with the porous polymer metal complex crystal particles becomes insufficient, and GO becomes multi-layered, which is undesirable because it tends to reduce the adsorption of the resulting composite.

[0064] In order to impart moldability to the crystal particles of the porous polymer metal complex, it is important that the crystal particle surface is in contact with the graphene oxides even partially. For this purpose, the mass % of GO in the composite is 0.01 to 30 mass%, more preferably 0.05 to 10 mass%. If the GO / porous polymer metal complex crystal particle ratio is too small, the amount of GO present on the surface of the porous polymer metal complex crystal particle is reduced, and the moldability of the obtained composite is reduced. If the GO / porous polymer metal complex crystal particle ratio is too large, the surface of the porous polymer metal complex crystal particle is covered with multiple layers of GO, and the adsorption of the obtained composite is reduced.

[0065] In the present invention, graphene oxide is used because it is easily obtained as an aqueous solution. A well-known method for producing graphene oxide is the Hammars method (WS Hummers et al., J. Am. Chem. Soc. (1958) 1339), which involves oxidizing graphite with KMnO4 in an acidic solution. Graphite is used as the raw material, and both natural and artificial graphite are available, and both can be used in the present invention. Artificial graphite is sold by Sigma-Aldrich. Natural graphite includes Madagascar Graphite from Iwamoto Minerals and Bay carbon (SP-1, 100Mesh) from Bay carbon Inc. In the production of the composite of the present invention described below, Madagascar Graphite from Iwamoto Minerals was used as the raw graphene oxide.

[0066] The graphene oxides used in the present invention are used as an aqueous solution using an aqueous solvent. In order to increase the reactivity with the porous polymer metal complex, it is important that the graphene oxides are dissolved in the solvent without agglomeration. It is known that the types and amounts of functional groups contained in graphene oxides vary depending on the preparation conditions. If the degree of oxidation is low, the amount of hydrophilic functional groups such as carboxylic acid is small and the water solubility is low, and if the degree of oxidation is too high, the area of ​​the graphene oxide film becomes small. The graphene oxide used in the present invention is not particularly limited as long as a graphene oxide aqueous solution of 0.0001 mass % to 8.0 mass % used for the synthesis of the composite can be prepared.

[0067] The concentration of the graphene oxide solution used in the composite of the present invention is 0.0001% by mass to 8.0% by mass, more preferably 0.001% by mass to 0.1% by mass. A composite with excellent properties can be obtained at a concentration lower than 0.001% by mass, but this is unrealistic because the amount of aqueous solution becomes huge, the process becomes complicated, and the drying time becomes extremely long. If the concentration is higher than 0.100% by mass, the graphene oxide is likely to polymerize in the solution to form multiple layers, and the porous coordination polymer is likely to be wrapped with a large amount of graphene, resulting in a decrease in the gas adsorption property of the obtained composite.

[0068] As a method for producing a composite of a porous polymer metal complex and graphene oxides, the so-called in situ method, in which a porous polymer metal complex is synthesized in the presence of graphene oxides, is well known. However, in this method, graphene oxides, which are essentially unnecessary for the reaction of metal ions, which are the raw materials of the porous polymer metal complex, with ligands, are present during the synthesis of the porous polymer metal complex, and the graphene oxides inhibit the reaction of the metal ions with the ligands. This may result in a decrease in yield of the obtained porous polymer metal complex, the generation of by-products, or a decrease in the adsorption properties of the obtained porous polymer metal complex. In addition, in the synthesis of a porous polymer metal complex, the reaction solvent often does not contain water, but in this method, the highly hydrophilic graphene oxides aggregate, which reduces the contact with the porous polymer metal complex, resulting in a decrease in moldability.

[0069] Unlike this method, the manufacturing method of the present invention mixes an aqueous solution of graphene oxides with already synthesized porous polymer metal complex crystal particles, so that the crystal particles of the porous polymer metal complex come into contact with graphene oxides that have been sufficiently exfoliated into a single layer or several layers. This composite is easy to form a stable molded body by applying pressure because the graphene oxides are likely to have strong interactions with each other. On the other hand, in the above-mentioned in situ method, various documents have revealed that the porous polymer metal complex crystal particles grow on the graphene oxides. According to this method, the graphenes are easily covered with the porous polymer metal complex crystal particles, and the graphene oxides are unlikely to interact with each other. For this reason, the in situ method has inferior moldability compared to the method of the present invention. In other words, the manufacturing method of the present invention can produce a molded body at a weaker pressure than the composite obtained by the in situ method, and when molded at the same pressure, it can be said that the shape retention (no breakage of the shape, no cracks) of the molded body obtained by the manufacturing method of the present invention is excellent.

[0070] The composite obtained by the production method of the present invention is produced by a process different from the above-mentioned in situ method, and the obtained composite can be distinguished from a composite produced by the in situ method by SEM and electrical conductivity.

[0071] The particle size of the porous polymer metal complex crystals can be measured by optical microscope if it is large, or scanning electron microscope if it is small, depending on the particle size. If there is a distribution in the particle size, the particle sizes of 20 particles selected from the microscope field of view can be measured and the average value can be used as the average particle size. Alternatively, it can be measured by a laser diffraction / scattering type particle size distribution (particle size distribution) measuring device such as LA-960 manufactured by Horiba, Ltd.

[0072] In the molded body of the composite of the present invention, the mechanism by which graphene oxides function as a binder is thought to be as follows, but this is merely a presumption and the present invention is not limited thereto.

[0073] In the molded body of the composite of the present invention, the particles of the porous polymer metal complex are partially in contact with or cross-linked with the graphene oxides (FIG. 2). In this way, the particles of the porous polymer metal complex are partially in contact with or cross-linked with the graphene oxides, so that the apparent particle size becomes larger and the particles are less likely to scatter as powder. In addition, since the graphene oxides have a wide molecular plane in which the benzene rings are conjugated, the graphene oxides have strong interactions with each other. Therefore, the composite of the porous polymer metal complex partially in contact with or cross-linked with the graphene oxides can be molded by simply compressing it lightly. Since there are gaps between the porous polymer metal complex and the graphene oxides, and the graphene oxides themselves have pores, the composite in which the porous polymer metal complex is partially in contact with or cross-linked with the graphene oxides has gas adsorption properties similar to those of the porous polymer metal complex, and the molded body of the present invention obtained with a weaker compression force than that without the graphene oxides has better gas adsorption and separation properties than a molded body produced without the graphene oxides. Furthermore, compared with a porous polymer metal complex formed without graphene, the composite of the present invention has excellent moldability and is less prone to powdering, and can be suitably used for gas adsorption and separation applications.

[0074] In addition, in the molded body of the composite of the present invention, as shown in FIG. 3, some of the crystal particles of the porous polymer metal complex are crosslinked by graphene oxides deformed into a rod-like or cylindrical shape. The principle is that excellent shaping properties are exhibited by such composites with graphene oxides having various shapes such as rod-like shapes, but as described in Patent Document 4, it is believed that the presence of a substance that bonds PCP particles together causes the PCP crystals to be gently bonded together, and the PCP particles are deformed by external force without becoming powder to give a molded body. Unlike the pulp fibers described in Patent Document 4, graphene oxides have strong interactions with each other, so that PCP particles crosslinked with graphene oxide can be easily shaped without being powdered because strong interactions are exhibited between the particles due to the interaction of the graphene oxides on the surface.

[0075] The composite of the present invention may be in a state in which the crystalline particles of the porous polymer metal complex are in partial contact with or cross-linked to the graphene oxides. As can be seen from the SEM photograph of Fig. 2, the crystalline particles of the porous polymer metal complex are in partial contact with the graphene oxides. Alternatively, as can be seen from the SEM photograph of Fig. 3, the crystalline particles of the porous polymer metal complex are partially cross-linked by the graphene oxides.

[0076] The method for producing a composite of the present invention is a method for partially contacting or crosslinking a porous polymer metal complex with graphene oxides by mixing the porous polymer metal complex with graphene oxides in an aqueous solvent. In this case, the porous polymer metal complex may be already complexed with other materials. For example, by immersing a composite of a porous polymer metal complex and pulp fibers disclosed in Patent Document 4 in an aqueous solution of graphene oxides, it is possible to partially contact or crosslink the crystal particles of the porous polymer metal complex complexed with pulp fibers with graphene oxides. As a result, it is possible to reduce powdering compared to pellets of a composite of a porous polymer metal complex and pulp fibers that is not complexed with graphene oxides. EXAMPLES

[0077] Hereinafter, the embodiment of the present invention will be described in more detail with reference to examples. Note that the examples shown below are merely examples, and the present invention is not limited to the examples shown below.

[0078] Synthesis of graphene oxide type A Madagascar Graphite from Iwamoto Minerals was used as the raw material, and was prepared by the method described below, and the final concentration was adjusted to 0.02 mass % with distilled water.

[0079] 1g of graphite was placed in a large, deep beaker of about 1L, and 40mL of concentrated sulfuric acid and 4.5mL of H3PO4 were added. While stirring at 150 rpm, 5g of KMnO4 was added while checking the temperature to be 35-40°C. After that, while stirring at 150 rpm for about 5 minutes, the temperature was heated with a heater to 35-40°C, and it was kept at 35-40°C for 4 hours. After 4 hours, the mixture of black powder and black viscous liquid was cooled on ice, and water was carefully added to about 400mL while stirring so that the temperature did not exceed 40°C. 8mL of hydrogen peroxide (about 30% by volume) diluted with water to 20mL was added in about 1 minute.

[0080] (i) Washing with water Centrifuge at 5000 rpm for about 5 minutes, and discard the aqueous layer thoroughly by decantation. Add 5% hydrochloric acid (70 mL of concentrated hydrochloric acid diluted to 500 mL) to the centrifuge tube up to 40 mL, shake vigorously by hand to disperse, centrifuge at 3500 rpm for about 5 minutes (extend to 10-15 minutes if sedimentation is poor), and discard the nearly colorless supernatant. This process of adding hydrochloric acid + centrifugation + decantation was repeated a total of 5 times. (ii) Washing with hydrochloric acid The centrifuge tube was filled with water up to 40 mL, vigorously shaken by hand for about 1 minute to disperse the particles, and centrifuged at 3,500 rpm for about 5 minutes. (iii) Re-rinsing with water The operations of adding water, dispersing, settling, and decanting were repeated a total of five times. (3) Extraction of graphene oxide The precipitate was added to 40 mL and centrifuged. This procedure of adding water, centrifuging, and decanting to collect graphene oxide was repeated about 3 to 8 times. The concentration of the obtained graphene oxide was 0.06 to 0.02 mass%.

[0081] Synthesis of graphene oxide type B Bay carbon (SP-1, 100 Mesh) from Bay Carbon Inc. was used as the raw material and prepared in the same manner as graphene oxide type A. The final concentration was adjusted to 0.02 mass% with distilled water to obtain graphene oxide type B.

[0082] Example 1-1 65 mg of UiO-66-H, a porous polymer metal complex sold by STREM, was dispersed in 10 mL of water and dispersed for 1 minute using a homogenizer (200 W). An aqueous solution (0.02% by mass) of graphene oxides A was prepared as a raw material so that 4.6% by mass of graphene oxides was contained in 14.4 mL of the porous polymer metal complex, and mixed with the porous polymer metal complex dispersion. After stirring for 30 minutes, the mixture was dried by freeze-drying to obtain 63 mg of sponge-like solids. The nitrogen adsorption properties were evaluated at 77 K using a Bellsoap Mini, and it was found to have the same adsorption properties as the raw material UiO-66-H. Observation using a SEM revealed that it was a composite in which UiO-66-H was in contact with or cross-linked with graphene oxides A and B (hereinafter referred to as the "UiO-66-H composite").

[0083] The operation performed in Example 1-1 was repeated to adjust the amount of the aqueous solution of graphene oxides A used, thereby producing composites having various graphene oxide contents in the products as Examples 1-2 to 1-5 and Comparative Examples 1-1 and 1-2. In Examples 1-4 and 1-5, aqueous solutions of 16.0 mass % and 27.0 mass % of graphene oxides A were used, respectively. Comparative Example 1-1 is an example that does not contain graphene oxides A, and Comparative Example 1-2 uses an aqueous solution of 0.005 mass % of graphene oxides A.

[0084] Comparative Example 1-3 A composite of PCP:UiO-66-H and graphene oxide type A was prepared by an in situ method. ZnCl4 (109 mg), dimethylformamide (3 mL), and concentrated hydrochloric acid (84 μL) were placed in a pressure vessel and irradiated with ultrasonic waves for 5 minutes. Terephthalic acid (174 mg) and 7.2 mg of a solid obtained by drying graphene oxides A were added, the vessel was covered, and ultrasonic waves were irradiated again for 10 minutes, and the vessel was allowed to react in an oven at 160°C for 20 hours. The solid obtained was filtered, washed with dimethylformamide and methanol, and dried to obtain 104 mg of a solid. The obtained composite was observed by SEM, but no crosslinking or partial contact due to graphene oxides was observed, as shown in Figure 5.

[0085] Comparative Example 1-4 The composite was prepared by solid-state synthesis using UiO-66-H as the raw PCP. 4.8 mg of the solid obtained by drying graphene oxide A was added to 100 mg of UiO-66-H and mixed in an agate mortar for 1 minute to obtain 108 mg of a solid. The obtained composite was observed by SEM, but no cross-linking or partial contact due to graphene oxide was observed, as shown in Figure 8.

[0086] The composites of each of the Examples and Comparative Examples were subjected to the following molding tests 1 and 2 and gas adsorption test. Formability test 1 20 mg of the complex was spread on a medicine wrapping paper to form a circle with a diameter of 19 mm, and a weight of 50 g with a diameter of 19 mm was placed on top of it and left to stand for 2 minutes. The complex obtained by this load application procedure was evaluated using a spatula as follows. The molded object can be lifted up with a spatula. Items that can be lifted but are deformed or break are rated △. Powdery items that cannot be lifted are marked as "X".

[0087] Formability test 2 Using a die with a diameter of 5 mm, 7 mg of the composite was pressed with a load of 2 kN for 2 minutes to obtain a disk-shaped compact. The obtained disk-shaped compact was dropped from a height of 5 cm and evaluated as follows. Those that have not broken and have maintained their disk-like shape are given a ◎. Those that have some cracks or chips but still retain their shape are marked as ○. Those that did not retain the disk shape at all were marked as x.

[0088] Gas Adsorption Test The obtained complex was heated at 170°C under reduced pressure for 6 hours, and about 50 mg of the obtained black solid was placed in a glass tube and subjected to nitrogen adsorption isotherm measurement (77K) using a gas adsorption apparatus, Bellsorp Mini II, manufactured by Microtrack Bell. The results of the above test are shown in Table 1.

[0089] [Table 1]

[0090] An example of the synthesis of a composite using a porous polymer metal complex (CPO-27(Ni)) different from UiO-66-H used in Example 1-1 will be described below.

[0091] Example 2-1 CPO-27(Ni) was used as the raw PCP. 65 mg of CPO-27(Ni) synthesized according to the literature (Dietzel et al., Chem. Commun. (2006) 959) was dispersed in 10 mL of water, and the dispersion operation was performed for 1 minute with a homogenizer (200 W). An aqueous solution of graphene oxides A as a raw material was prepared so that 2.8 mass % of graphene oxides A was contained in 14.4 mL with respect to the porous polymer metal complex, and mixed with the porous polymer metal complex dispersion. After stirring for 30 minutes, it was dried by freeze-drying to obtain 99 mg of a sponge-like solid.

[0092] Using the same method as in the above example, four more composites with different contents of graphene oxides A were synthesized and evaluated. The same operation as in Example 2-1 was repeated, but the amount of graphene oxides A present in the aqueous graphene oxide A solution was changed to synthesize composites containing various graphene oxides A in mass % (Examples 2-2 to 2-5).

[0093] The nitrogen adsorption characteristics were evaluated at 77K using a Bellsorp Mini, and it was found to have the same adsorption characteristics as the raw material CPO-27(Ni) itself. Observation using a SEM revealed that it was a composite in which CPO-27(Ni) particles were crosslinked with rod-shaped graphene oxide type A.

[0094] Comparative Example 2-1 Furthermore, a composite not containing graphene oxides A was prepared as Comparative Example 2-1 in the same manner as in the above Example, except that the same amount of water was used instead of the graphene oxides A aqueous solution.

[0095] Comparative Example 2-2 This is an example of in situ synthesis of a composite of CPO-27(Ni) and graphene oxides using Ni(OAc)2·4H2O as the raw PCP. In a 25 mL pressure vessel, 180 mg of Ni(OAc)2·4H2O, 5 mL of water, 72 mg of 2,5-dihydroxyterephthalic acid, and 11.4 mg of the solid obtained by drying graphene oxides A were added, followed by tetrahydrofuran (5 mL), and the mixture was reacted at 110°C for 70 hours. After the reaction, the mixture was filtered, washed with water and ethanol, and dried to obtain 145 mg of a solid. The obtained composite was observed by SEM, but no crosslinking or partial contact due to graphene oxides was observed, as shown in Figure 6.

[0096] Comparative Example 2-3 This is an example of a solid synthesis method using CPO-27(Ni) as the raw PCP. 2.9 mg of the solid obtained by drying graphene oxide A was added to 100 mg of CPO-27(Ni) and mixed in an agate mortar for 1 minute. The obtained composite was observed by SEM, but no cross-linking or partial contact due to graphene oxide was observed, as shown in Figure 9. The obtained composite was subjected to the moldability tests 1 and 2 and the gas adsorption test in the same manner as in Example 1-1. The evaluation results are shown in Table 2.

[0097] [Table 2]

[0098] Example 3-1 An example of the synthesis of a complex using CAU-10-H as the raw PCP is shown below. 100 mg of CAU-10-H, synthesized according to the literature (Stock et al., Chem. Mater. (2013) 17), was dispersed in 10 mL of water and dispersed for 1 minute using a homogenizer (200 W). An aqueous solution of graphene oxides A as a raw material was prepared so that 0.71 mass % of graphene oxides A was contained in 14.4 mL of the porous polymer metal complex, and mixed with the porous polymer metal complex dispersion. After stirring for 30 minutes, the mixture was dried by freeze-drying to obtain 86 mg of a sponge-like solid.

[0099] The nitrogen adsorption characteristics were evaluated at 77K using a Bellsoap Mini, and it was found to have the same adsorption characteristics as the raw material CAU-10-H itself. Observation using a SEM revealed that it was a composite in which CAU-10-H particles were crosslinked by rod-shaped graphene oxide A.

[0100] Furthermore, by changing the amount of graphene oxides A present in the graphene oxide aqueous solution, four more types of composites (Examples 3-2 to 3-5) with different contents of graphene oxides A were synthesized in the same manner as in the above examples, and Comparative Example 3-1, which did not contain graphene oxides A, was also synthesized. Moldability tests 1 and 2 and a gas adsorption test were performed in the same manner as in Example 1-1. The evaluation results are shown in Table 3.

[0101] [Table 3]

[0102] Example 4-1 An example of the synthesis of a composite using ZIF-8 as the raw PCP is shown below. 100 mg of ZIF-8, synthesized according to the literature (Lively et al., J. Phys. Chem. C (2014) 20727), was dispersed in 10 mL of water and dispersed for 1 minute with a homogenizer (200 W). An aqueous solution of graphene oxide A as a raw material was prepared so that 1.86 mass% of graphene oxide A was contained in 14.4 mL of the porous polymer metal complex, and mixed with the porous polymer metal complex dispersion. After stirring for 30 minutes, the mixture was dried by freeze-drying to obtain 8665 mg of a sponge-like solid.

[0103] The nitrogen adsorption characteristics were evaluated at 77K using a Bellsorp Mini, and it was found to have the same adsorption characteristics as the raw material ZIF-8 itself. Observation using a SEM revealed that it was a composite in which ZIF-8 particles were crosslinked by rod-shaped graphene oxides A.

[0104] Furthermore, by changing the amount of graphene oxides A present in the graphene oxide aqueous solution, three more types of composites (Examples 4-2 to 4-4) with different graphene oxides A contents were synthesized by the same method as in the above example.

[0105] In addition, as examples of a composite having a very high content of graphene oxides A, a composite of Comparative Example 4-1 and a composite of Comparative Example 4-2 not containing graphene oxides A were synthesized by the same method as above.

[0106] Comparative Example 4-3 This is an example of in situ production of a composite of ZIF-8 and graphene oxide using Zn(NO3)2-6H2O as the raw material PCP. A stirrer was placed in a 500 mL recovery flask, 2.04 g (6.8 mmol) of Zn(NO3)2-6H2O and 11.4 mg of dried graphene oxide solid were added, 139 mL of methanol was added to dissolve, and the mixture was subjected to ultrasonic waves for 30 minutes. Separately, 2.25 g (27.4 mmol) of 2-methylimidazole, 2.18 mL (27.4 mmol) of 1-methylimidazole, and 139 mL of methanol were placed in a 500 mL Erlenmeyer flask and dissolved. While vigorously stirring the 500 mL eggplant flask, the entire content of the 500 mL Erlenmeyer flask was dropped at 100 mL / min, and after 24 hours, the mixture was filtered, washed with methanol, and dried to obtain 191 mg of a solid. The obtained composite was observed by SEM, but no cross-linking or partial contact due to graphene oxides was observed, as shown in Figure 7.

[0107] Comparative Example 4-4 This is an example of a solid synthesis method using ZIF-8 as the raw material PCP. 7.5 mg of dried graphene oxide solid was added to 100 mg of ZIF-8 and mixed in an agate mortar for 1 minute. The obtained solid was observed by SEM, but no cross-linking or partial contact due to graphene oxide was observed, as shown in Figure 10. The obtained composite was subjected to the moldability tests 1 and 2 and the gas adsorption test in the same manner as in Example 1-1. The evaluation results are shown in Table 4.

[0108] [Table 4]

[0109] Example 5 ELM-31b was used as the raw PCP. 72 mg of flexible porous polymer metal complex ELM-31b, synthesized according to the literature (Patent Application 2004-39881), was dispersed in 10 mL of water, and the dispersion operation was performed for 1 minute using a homogenizer (200 W). An aqueous solution of graphene oxides A was prepared as a raw material so that 3.9 mass % of graphene oxides A was contained in 14.4 mL relative to the porous polymer metal complex, and mixed with the porous polymer metal complex dispersion. After stirring for 30 minutes, the mixture was dried by freeze-drying to obtain 47 mg of a sponge-like solid.

[0110] Comparative Example 5 As Comparative Example 5, a composite containing no graphene oxides was prepared in the same manner as in Example 5.

[0111] The nitrogen adsorption characteristics were evaluated at 77K using a Bellsorp Mini, and showed an adsorption amount equivalent to that of the raw material ELM-31b, and the gate-type adsorption isotherm was characteristic of the flexible porous polymer metal complex ELM-31b, as shown in Figure 4. This indicates that the composite of the flexible porous polymer metal complex with graphene oxide type A does not inhibit the structural change of the porous polymer metal complex during gas adsorption. Observation by SEM revealed that the composite was made of ELM-31b particles crosslinked by rod-shaped graphene oxide type A.

[0112] [Table 5]

[0113] Example 6 The composite was synthesized using graphene oxide type B as the raw material. Instead of Madagascar Graphite from Iwamoto Minerals, Bay carbon (SP-1, 100Mesh) from Bay Carbon Inc. was used as the graphene to prepare a graphene oxide aqueous solution B. The obtained aqueous solution was dried and observed by SEM. It was found that the diameter of one sheet of graphene oxide B was approximately 20 μm, which was smaller than that of graphite A.

[0114] By using the graphene oxide aqueous solution B instead of the graphene oxide aqueous solution A in the same manner as in Example 1 and adjusting the amount of the graphene oxide B aqueous solution, composites containing graphene oxide B at various mass % were synthesized, and moldability tests and adsorption evaluations were performed (Examples 6-1 to 6-4). The obtained composites showed adsorptivity almost equivalent to that of the raw material PCP used in the synthesis. In addition, a disk molded into a plate shape using a 50 mg weight could be lifted with a spatula in the same manner as in Example 1. The evaluation results of the moldability tests 1 and 2 and the gas adsorption test are shown in Table 6.

[0115] [Table 6]

[0116] A composite synthesized by the production method of the present invention and a composite synthesized by the in situ method can be clearly distinguished by their electrical resistance values.

[0117] Using UiO-66-H or CPO-27(Ni) as the porous polymer metal complex, the amount of graphene oxides A was changed in the same manner as in Examples 1 and 2 to prepare composites having various graphene oxides A contents.

[0118] Examples 7-1 to 7-3 20 mg of the UiO-66-H composite or CPO-27(Ni) composite that had not been subjected to any heat treatment or other treatment was packed into a cylinder with a diameter of 1 cm, and after inserting a metal piston, 10 atmospheres of air pressure was applied and maintained for 1 minute. When the electrical resistance was measured from above and below the disk with a tester, the electrical resistance was infinite, and unlike the heat-treated composite, it did not exhibit electrical conductivity (Examples 7-1, -2, -3).

[0119] Comparative Examples 7-1 to 7-3 In addition, as examples of composites by the in situ method, composites having various contents of graphene oxides A were prepared in the same manner as in Comparative Example 1-3 and Comparative Example 2-2 (Comparative Examples 7-1, -2, -3). The composites synthesized by the manufacturing method of the present invention and the in situ method were subjected to electrical conductivity evaluation in the same manner as above. The results are shown in Table 7.

[0120] [Table 7]

[0121] None of the composites obtained by the method of the present invention were conductive, whereas the composites obtained by the in situ method were conductive, indicating that the mixed state of PCP and graphene oxides, as well as the physical properties of graphene oxide and the composites, are different.

[0122] Gas Permeability Test Approximately 25 mg of the graphene oxide A (4.6 mass%) and UiO-66-H composite produced by the method of the present invention was placed in a die with a diameter of 5 mm, a piston was inserted, a load of 6 N was applied, and the mixture was held for 1 minute to form a thin disk. This disk was sandwiched between two doughnut-shaped pieces of silicone rubber, and 132.6 kPa of carbon dioxide or nitrogen gas was pressurized to one side of the disk, and the time it took for the pressure to drop to 131.5 kPa was measured. The permeation rate of carbon dioxide was 2.7 times that of nitrogen, indicating that a carbon dioxide selective permeable membrane was formed and that it could be used for gas separation.

Claims

1. The present invention relates to a method for producing a flexible porous polymer metal complex comprising the steps of: the flexible porous polymer metal complex is a porous polymer metal complex having a one-dimensional chain structure or a laminated type porous polymer metal complex having a two-dimensional network; The graphene oxides are contained in an amount of 0.01 to 30% by mass, And the composite has infinite electrical resistance.

2. The flexible porous polymer metal complex having a one-dimensional chain structure is represented by the formula: [G(H) 2 (I)], where G is a transition metal ion, H is a first ligand, and I is a second ligand, or G 2 (J) 3 (L 3 ) 4 2. The complex of claim 1, wherein G is a transition metal ion, J is a ligand, and L is a monovalent counter ion.

3. The two-dimensional network laminated flexible porous polymer metal complex is generally called Kagome type, and has the formula: [GH] (wherein G represents a transition metal ion and H represents a ligand), or generally called ELM, and has the formula: [GHX 2 2. The complex according to claim 1, wherein G represents a transition metal ion, H represents a 4,4-bipyridyl, and X represents a monovalent counter ion.

4. The present invention relates to a method for producing a flexible porous polymer metal complex comprising the steps of: the flexible porous polymer metal complex is a porous polymer metal complex having a one-dimensional chain structure or a laminated type porous polymer metal complex having a two-dimensional network; A method for producing a composite containing 0.01 to 30% by mass of the graphene oxides, the method comprising: mixing the flexible porous polymer metal complex dispersed in water with an aqueous solution containing the graphene oxides at a concentration of 0.001 to 0.100% by mass.

5. The flexible porous polymer metal complex having a one-dimensional chain structure is represented by the formula: [G(H) 2 (I)], where G is a transition metal ion, H is a first ligand, and I is a second ligand, or G 2 (J) 3 (L 3 ) 4 (wherein G is a transition metal ion, J is a ligand, and L is a monovalent counter ion),

6. The two-dimensional network laminated flexible porous polymer metal complex is generally called Kagome type, and has the formula: [GH] (wherein G represents a transition metal ion and H represents a ligand), or generally called ELM, and has the formula: [GHX 2 5. The method for producing a complex according to claim 4, wherein G represents a transition metal ion, H represents a 4,4-bipyridyl, and X represents a monovalent counter ion.

7. A molded article comprising the composite material according to any one of claims 1 to 3.

8. A gas adsorbent comprising the molded article according to claim 7.

9. A gas separation apparatus using the gas adsorbent according to claim 8.

10. A gas storage device using the gas adsorbent according to claim 8.

Citation Information

Patent Citations

  • Graphene oxide coated metal organic framework material and preparation method thereof

    CN106669608A

  • Method for preparing graphene / MOF (metal-organic framework) porous composite material aquagel and graphene / MOF porous composite material aerogel

    CN107215863A

  • Preparation method of graphene / metal organic frame aerogel adsorbing / catalyzing material

    CN107376837A

  • New organometallic complex and gas adsorbent

    JP2000109493A

  • Molded article comprising porous metal complex, and filter prepared using the same

    JP2015066512A